A2.10 SLE associated UBE2L3 haplotype modulates plasma cell differentiation via genotypic regulation of NF-κB. (13th February 2015) - Vyse, S; Shields, AM; Boeltz, S; Leirer, D; Gordon, PA; Spector, TD; Lehner, PJ; Walczak, H; Vyse, TJ; Lewis, MJ
Abstract : Background and objectives: Genome-wide association studies have identified a strong association between a single risk haplotype of the UBE2L3 gene and systemic lupus erythematosus (SLE). UBE2L3 is an E2 ubiquitin-conjugating enzyme that critically regulates ubiquitination by the linear ubiquitin chain assembly complex (LUBAC) with consequent effects on NF-kB signalling and inflammatory responses. Herein, we dissect the role of UBE2L3 in regulating NF-kB signalling in human B-cells and monocytes and demonstrate the risk haplotype drives plasmablast and plasma cell expansion in patients with SLE. Materials and methods: UBE2L3 genotype data from GWAS in SLE was imputed using 1000 Genomes reference data. UBE2L3 function and signalling pathways were studied in vitro in HEK293 cells, or ex vivo using B cells and monocytes from healthy individuals or SLE patients (NF-kB translocation by Imagestream, multicolour flow cytometry of B cell subsets) stratified by UBE2L3 genotype. Parameters of SLE disease activity were collected and correlated with flow cytometry results. Results: Data from SLE GWAS, imputed to 1000 Genomes level identified rs140490 as the most strongly associated UBE2L3 SNP, located at -270bp of the promoter region (p = 8.6 × 10–14; OR 1.30, 95% CI: 1.21–1.39). Microarray/western blot studies found that the rs140490 risk allele correlated with increased UBE2L3 expression in human B cells and monocytes. Overexpression of UBE2L3 in combination with LUBAC in HEK293-NF-kB reporter cell lines led to marked upregulation of NF-kB activity, which was abolished by a dominant-negative mutant UBE2L3[C86S]. RNAi blockade of UBE2L3 antagonised TNF signalling by inhibiting IκBα processing. UBE2L3 expression was 3–4-fold elevated in peripheral blood plasmablasts and plasma cells (p < 0.0001), with increased UBE2L3 expression in plasma cells from SLE patients compared to controls (p = 0.01). The T/T genotype at rs140490 was associated with a significant expansion in plasmablast and plasma cell populations in SLE patients (both p < 0.001), and showed a trend to correlation with increased SLEDAI scores (p = 0.06). Imagestream analysis demonstrated that rs140490 genotype correlated with both basal NF-kB activation in healthy individuals, as well as the sensitivity of NF-kB to CD40 stimulation in B cells and TNF stimulation in monocytes. Conclusions: The UBE2L3 risk haplotype exerts a critical rate-limiting effect on TNF and CD40 signalling through regulation of LUBAC and NF-kB activation. This is the first demonstration that a complex trait variant at UBE2L3 regulates both basal NF-kB activation and sensitivity of NF-kB to stimulation in ex vivo human cells, resulting in accelerated B cell differentiation in SLE.